Schools’ Provision for Students at Risk of Not Achieving: Evaluation of an Education Review Office Evaluation Report - Keith Greaney (New Zealand Journal of Teachers' Work)
A recent report published by the Education Review Office (2008) found that most primary schools were able to adequately identify their students who were at risk of not achieving (in literacy). The basis for their findings was that most schools had apparently indicated that they had used the current assessment tools for identification purposes. However, a second finding noted in the report was that most schools were less able to show that they effectively used the data to inform their teaching practices. The concern expressed in this paper is that the evaluation report is merely confirmation that, in general, ERO appears to be satisfied with the appropriateness of the current literacy assessment tools as being suitable for identifying all students who were at risk of not achieving. Given the vast research literature implicating poor and/or inefficient phonological processing skills as being the causal link to most early literacy-related underachievement, it is suggested in this paper that the ERO report could have noted the absence of such assessment tools, and therefore any subsequent teaching interventions that addressed these issues.